Pengaruh Marketing Mix 7P Terhadap Keputusan Pembelian di Coffee Shop Solok Radjo Kecamatan Lembah Gumanti Kabupaten Solok: Pengaruh Marketing Mix 7P Terhadap Keputusan Pembelian di Coffee Shop Solok Radjo Kecamatan Lembah Gumanti Kabupaten Solok - Alvindo Dermawan; Dian Fauzi; Oki Junia Putra (JURNAL ILMIAH AGRINECA, 2026)
A coffee shop is a place for eating and drinking that offers a relaxed atmosphere without strict rules and typically features coffee as a special menu item alongside snacks or fast food. Solok Radjo Coffee Shop, located in Alahan Panjang, has an interesting theme with a glamping ground that enhances its appeal to consumers and uses self-produced and processed raw materials. This study aims to: 1) describe the 7P marketing mix's impact on purchasing decisions at Solok Radjo Coffee Shop, and 2) analyze the influence of the 7P marketing mix on purchasing decisions at Solok Radjo Coffee Shop. Primary data was used in this study, collected through interviews, observations, and questionnaires. The analysis techniques used include quantitative descriptive methods, validity and reliability tests, classical assumption tests, multiple regression analysis, T-tests, F-tests, and the determination coefficient test (R2). The results showed that the customer base of Solok Radjo Coffee Shop is dominated by young, highly educated, unmarried women. Furthermore, the 7P variables for Solok Radjo Coffee Shop were significant except for place and promotion.